Metabolic regulation and consequences of an altered microenvironment in cancer cell lines - Bose, Ujjal (2019)
Tumours are commonly associated with a shift in cellular metabolism to establish an acidic microenvironment that is further exacerbated by hypoxia. Such changes in extracellular pH (pHe) and oxygen tension (PO2) alter ion homeostasis effecting cancer hallmarks. High intracellular potassium (K+) is a key determinant of membrane potential driving cellular function including proliferation and migration. Cancer cells overexpress several K+ channel subtypes, modulated by metabolic factors including pHe. We hypothesise that acidic and hypoxic microenvironment affects cancer cell behaviour mediated, in part, by K+ transport involving K+ channels. We aimed to develop and test the effects of a normal microenvironment (pHe 7.4; PO2 0.21 atm) and modified (low pHe 6.3; low PO2 0.029 atm) culture conditions on K+ channel gene expression (by qPCR) and their contributions to cell proliferation in the SK-OV-3, MCF-7 and OE-19 cancer cell lines. Altered pHe predominantly affected gene expression of pH-sensitive (KCNK9 (TASK-3); KCNK17 (TALK-2)) and voltage-gated (KCNH1 (eag); KCNH2 (HERG)) K+ channels in SK-OV-3 cells. TASK-3 channel expression was upregulated in low pHe & PO2 compared with normal pHe & PO2 (P < 0.05). mRNA expression for KCNH1 and KCNH2 was decreased in low pHe compared with normal pHe & PO2 for all three cell lines tested. Cell proliferation of SK-OV-3 cells was inhibited by the TASK-3 blocker methanandamide and the HERG blocker, E4031, most significantly in low pHe & PO2. Live-cell imaging methods deploying pH-sensitive (BCECF-AM, carboxy-SNARF-AM, pH nanosensor) fluorophores and the K+-sensitive (nigericin) ionophore were also developed and optimised in order to study the cellular responses of cancer cells following acid loading using the ammonium pre-pulse method. Values for the Intrinsic Buffering Capacity (βI), steady state pHi recovery and net acid extrusion (NAE) of SK-OV-3 and MCF-7 cells in response to altered pHe & PO2 were derived. Results demonstrated that SK-OV-3 cells had lower buffering capacity in acidic pHe than MCF-7 cells. In altered pHe & PO2, NaHCO3-dependent (extrinsic) buffering promoted recovery of pHi from acute acidification (P < 0.001) in both SK-OV-3 and MCF-7 cells. Low pHe & PO2 culture conditions significantly enhanced βI as reflected through increased NAE of cancer cells. Finally, altered K+ flux under low pHe & PO2 appeared to involve TASK-3 channels as shown by inhibition with methanandamide in SK-OV-3 and MCF-7 cells. Cancer cell behaviour is modified by an acidic, low oxygen microenvironment, in part involving the TASK-3 channel. These inferences are based on culture methodology developed in this study that will emerge as pivotal for future investigations of the role of these channels in response to the cancer environment.